Activity-Based Detection of Cannabinoids in Serum and Plasma Samples. (1st June 2018) - Cannaert, Annelies; Storme, Jolien; Hess, Cornelius; Auwärter, Volker; Wille, Sarah M R; Stove, Christophe P
Abstract: BACKGROUND: Synthetic cannabinoids are the largest group of new psychoactive substances monitored by the European Monitoring Centre of Drugs and Drug Addiction. The rapid proliferation of novel analogs makes the detection of these new derivatives challenging and has initiated considerable interest in the development of so-called "untargeted" screening strategies to detect these compounds. METHODS: We developed new, stable bioassays in which cannabinoid receptor activation by cannabinoids led to recruitment of truncated β-arrestin 2 (βarr2) to the cannabinoid receptors, resulting in functional complementation of a split luciferase, allowing readout via bioluminescence. Aliquots (500 μL) of authentic serum (n = 45) and plasma (n = 73) samples were used for simple liquid–liquid extraction with hexane:ethyl acetate (99:1 v/v). Following evaporation and reconstitution in 100 μL of Opti-MEM ® I/methanol (50/50 v/v), 10 μL of these extracts was analyzed in the bioassays. RESULTS: Truncation of βarr2 significantly (for both cannabinoid receptors; P = 0.0034 and 0.0427) improved the analytical sensitivity over the previously published bioassays applied on urine samples. The new bioassays detected cannabinoid receptor activation by authentic serum or plasma extracts, in which synthetic cannabinoids were present at low- or sub-nanogram per milliliter concentration or in which Δ 9 -tetrahydrocannabinol was present at concentrations >12 ng/mL. For synthetic cannabinoid detection, analytical sensitivity was 82%, with an analytical specificity of 100%. CONCLUSIONS: The bioassays have the potential to serve as a first-line screening tool for (synthetic) cannabinoid activity in serum or plasma and may complement conventional analytical assays and/or precede analytical (mass spectrometry based) confirmation.